The bond as a guideline for the construction of integrality in the Family Health Strategy - Viegas, Selma Maria da Fonseca; Penna, Cláudia Maria de Mattos (Rev Rene, 2012)
The bond between family health team and the enrolled population is a guideline for the comprehensive care. This is a multiple case study of holistic and qualitative approach based on the Quotidian Comprehensive Sociology, clipping of a PhD thesis which aimed to understand the construction of integrality practices in health in the daily work of family health teams and the managers of three boroughs. The informants were 48 health workers. The results show the link as the essential guideline for the consolidation of the integrality in health encouraging the user´s autonomous participation in the production of one‟s health. However, the staff‟s turnover interferes in the dynamics of daily work and in building links with the families, which directly involves consolidation of the local strategy. It is concluded that the link may be a collective and consolidated practice of the teams with the population in the construction of integrality in the health care.